2021
DOI: 10.17582/journal.pjar/2021/34.4.748.757
|View full text |Cite
|
Sign up to set email alerts
|

Function of Ultraviolet Radiation (UV-B) Light on the Survival of Red Flour Beetle Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) and their Body Fitness

Abstract: R ed flour beetle (Tribolium castaneum) (Herbst) (Coleoptera: Tenebrionidae) is the major and a worldwide distribution insect pest in store grain that causes quantitative and qualitative damages to flour by feeding. T. castaneum is the most widespread pest in flour mills, warehouses and grocery stores (Garcia et al., 2005; Padin et al., 2002). Losses of grain estimated that post-harvest grain losses exceed $500 million annually and most of the losses are results of organism source such as insects or mycoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Three studies on longer wavelengths have been reported. Khan et al (2021) treated various life stages of T. castaneum with UV-B. In proportion to exposure time, the duration of egg incubation and larval and pupal development were lengthened, and egg hatch, longevity, larval, pupal and adult weights were reduced, and larval and pupal mortality increased.…”
Section: Coleopteramentioning
confidence: 99%
“…Three studies on longer wavelengths have been reported. Khan et al (2021) treated various life stages of T. castaneum with UV-B. In proportion to exposure time, the duration of egg incubation and larval and pupal development were lengthened, and egg hatch, longevity, larval, pupal and adult weights were reduced, and larval and pupal mortality increased.…”
Section: Coleopteramentioning
confidence: 99%
“…Flea beetle and fruit fly was observed on white and yellow light colour as compared with green, blue and red colure lights (table-2). Various colors of lights have significantly effect on orientation, locomotion, feeding, mating, ovipositor, adult emergence, and the development of insects (Ahmed et al, 2021;Khan et al, 2021). Semeao et al (2011) found that factors such as light intensity in contrast with color background may have impact on level of adults captured.…”
mentioning
confidence: 99%